ChemInform Abstract: Benzimidazoles and Benzoxazoles via the Nucleophilic Addition of Anilines to Nitroalkanes. Issue 30 (July 2015) - Aksenov, Alexander V.; Smirnov, Alexander N.; Aksenov, Nicolai A.; Bijieva, Asiyat S.; Aksenova, Inna V.; Rubin, Michael
Abstract The reaction of phenylenediamines and 2‐aminophenols (I) with nitroalkanes (II) in PPA leads to desired benzimidazoles and benzoxazoles (III) in high yields, whilst the reaction with 2‐nitro‐1‐phenylethan‐1‐one (IV) affords unexpected 2‐phenyl substituted products.